The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1164/rccm.202107-1761oc
|View full text |Cite
|
Sign up to set email alerts
|

Multinight Prevalence, Variability, and Diagnostic Misclassification of Obstructive Sleep Apnea

Abstract: At a Glance Commentary (191/200) Scientific Knowledge on the SubjectRecent studies that have assessed obstructive sleep apnea (OSA) over several consecutive nights indicate that OSA severity can vary markedly from night-to-night which may have important implications for diagnosis, management, and prevalence estimates. Prior to recent advances in non-invasive home sleep monitoring technology, it was not feasible to examine night-to-night variation in OSA severity and its potential impact on diagnostic classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 32 publications
4
60
0
Order By: Relevance
“…However, obstructive sleep apneas are more common in the general population 52 . An assessment for OSA based on a single night may result in a certain degree of exposure misclassification 53 , which could affect the precision, but would not bias our estimates. The T90 parameter is not able to differentiate hypoxia caused by OSA from nocturnal hypoxia of other etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…However, obstructive sleep apneas are more common in the general population 52 . An assessment for OSA based on a single night may result in a certain degree of exposure misclassification 53 , which could affect the precision, but would not bias our estimates. The T90 parameter is not able to differentiate hypoxia caused by OSA from nocturnal hypoxia of other etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly this seems most important when differentiating between no sleep apnea and mild OSA, and mild and moderate OSA. Here Lechat and colleagues add important clarity ( 6 ). They showed that an average of 21% of diagnoses (no OSA vs. OSA) would be false negative on a single night study.…”
mentioning
confidence: 99%
“…In this issue of the Journal , Lechat and colleagues (pp. 563–569 ) set out to assess the prevalence of OSA (using a cutoff for diagnosis of AHI ⩾15), and night-to-night variation in AHI over a far longer period than in previous studies, and with a large sample size to understand the impact on diagnostic certainty ( 6 ). This was made feasible by using a contactless noninvasive diagnostic device (Withings Sleep Analyzer) placed under the user’s mattress at home.…”
mentioning
confidence: 99%
“…Obstructive sleep apnea (OSA), characterized by repetitive upper airway collapse during sleep, is estimated to affect nearly 1 billion people worldwide 1,2. OSA is a common comorbidity in people undergoing surgical procedures, with rates as high as 91% in those undergoing bariatric surgery 3.…”
mentioning
confidence: 99%
“…airway collapse during sleep, is estimated to affect nearly 1 billion people worldwide. 1,2 OSA is a common comorbidity in people undergoing surgical procedures, with rates as high as 91% in those undergoing bariatric surgery. 3 OSA is an important risk factor for adverse postoperative outcomes including cardiac complications, opioid-induced ventilatory depression, and unplanned intensive care unit transfers.…”
mentioning
confidence: 99%